Pengaruh Intellectual Capital dan Islamic Corporate Governance Disclosure terhadap Kinerja Keuangan: Peran Islamic Corporate Social Responsibility Disclosure sebagai Variabel Mediasi - W Djuanda; Amries Rusli Tanjung; Kamaliah Kamaliah (Jurnal Ekonomi, 2019)
This study aims to determine the effect of intellectual capital and Islamic corporate governance on the partial disclosure of financial performance. Furthermore, this study also examines the role of Islamic corporate social responsibility disclosure as mediating the relationship between intellectual capital and Islamic corporate governance disclosure and financial performance. The population in this study is Islamic general banking registered at Bank Indonesia (BI). The sampling method used in this study was purposive sampling, in order to obtain 49 samples. This study uses secondary data obtained from the each of Islamic general bankingwebsite. The statistical method used to test the research hypothesis is the Structural Equation Model (SEM) based on Partial Least Square (PLS) with the help of the WarpPLS 6.0 program. The results of this study prove that Islamic corporate governance disclosure has a positive and significant effect on Islamic corporate social responsibility disclosure, while intellectual capital has no effect on Islamic corporate social responsibility disclosure. Then Islamic corporate social responsibility disclosure has no effect on financial performance. Furthermore, Islamic corporate social responsibility disclosure cannot show its role as a mediation of the relationship between intellectual capital and Islamic corporate governance, a partial disclosure of financial performance.